Design of a Zwitterion Polymer Electrolyte Based on Poly[poly (ethylene glycol) methacrylate]: The Effect of Sulfobetaine Group on Thermal Properties and Ionic Conduction. Issue 1 (August 2017) - Guzmán, Gregorio; Nava, Dora P.; Vazquez‐Arenas, Jorge; Cardoso, Judith
Abstract : Polymer electrolytes are expected to play an overriding role in the development of sustainable lithium ion batteries. In this study, amorphous poly(poly(ethylene glycol) methacrylate) (pPEGMA) and pPEGMA functionalized with sulfobetaine pendants (pMPS8) are synthesized, and subsequently formulated with LiPF6 to be assessed as solid polymer electrolytes (SPE). The polymer properties are investigated using Differential scanning calorimetry (DSC), X‐ray diffraction (XRD), Attenuated total reflection Fourier transform infrared (FTIR) and Electrochemical Impedance Spectroscopy (EIS). These experimental analyses are used to account for the effects of a methacrylate‐type polymer as an alternative to improve Li + mobility across the polymer, and synergic benefits of its functionalization with sulfobetaine groups. pPEGMA displayed a Tg around −49 °C, which increases in the presence of the lithium salt to −38 °C due to the interactions arising between Li + ions and the polymer, as confirmed by XRD and FTIR characterizations. The ionic conductivity of the pPEGMA/LiPF6 system is 6.92 × 10 −6  S cm −1, which denotes a partial dissociation of LiPF6 as a result of the formation of ion pairs, detected by the structural characterization. The functionalization of pPEGMA is an efficient method to decrease the Tg down to −53 °C, suggesting that pMPS8 keeps amorphous pPEGMA matrix allowing mobility of polymer chains by the presence of the sulfobetaine pendants. Evidence of this behavior is determined with the chemical and structural evaluations, and clearly observed in the increase of ionic conductivity by two orders of magnitude. Although the Tg of the pMPS8/LiPF6 system considerably augments to −24 °C, its effects are negligible in ionic conductivity (3.22 × 10 −5  S cm −1 ), indicating that a relatively low stiff backbone arises in pMPS8 structures, which is not influenced by the presence of LiPF6 due to the strong charge delocalization generated by the sulfobetaine groups.